The Effect of Polarized Training on Functional Threshold Power in Road Bike Cyclists - Triana Puspa Dewi; Yadi Sunaryadi; Widi Kusumah (Journal of Physical Education Health and Sport, 2025)
Evaluating the effectiveness of training programs by monitoring athletes’ skills makes a crucial contribution to endurance sports such as road cycling. The purpose of this study was to examine the effect of polarized training on FTP (Functional Threshold Power), which is defined as the maximum power that an athlete can maintain for approximately 60 minutes. There were 5 expert cyclists aged 17-20 years from ISSI Kota Bandung, involving pre-test and post-test stages using an experimental method. 80% of the training sessions were low intensity, with the remaining 20% being high intensity, and participants had to follow a polarized training schedule for a period of 6 weeks. A Wahoo KICKR smart trainer with MyWhoosh FTP20 settings was used to assess FTP. A t-test was performed after a Shapiro-Wilk test to check whether the data was normally distributed or not in the statistical process. Outcomes indicated a substantial FTP improvement, rising from 3,514 to 3.820 W/kg (t = -6.372, p = 0.003 < 0.05). Polarized training significantly increases FTP among road cyclists, as shown in these findings. This demonstrates that the use of polarized intensity allocation is a scientifically proven approach to increasing FTP, an essential measure of cycling skill or ability marked by FTP.